Homogentisate Phytyltransferase Activity Is Limiting for Tocopherol Biosynthesis in Arabidopsis - Collakova, Eva (American Society of Plant Biologists, 2003)
Tocopherols are essential components of the human diet and are synthesized exclusively by photosynthetic organisms. These lipophilic antioxidants consist of a chromanol ring and a 15-carbon tail derived from homogentisate (HGA) and phytyl diphosphate, respectively. Condensation of HGA and phytyl diphosphate, the committed step in tocopherol biosynthesis, is catalyzed by HGA phytyltransferase (HPT). To investigate whether HPT activity is limiting for tocopherol synthesis in plants, the gene encoding Arabidopsis HPT, HPT1, was constitutively overexpressed in Arabidopsis. In leaves, HPT1 overexpression resulted in a 10-fold increase in HPT specific activity and a 4.4-fold increase in total tocopherol content relative to wild type. In seeds, HPT1 overexpression resulted in a 4-fold increase in HPT specific activity and a total seed tocopherol content that was 40% higher than wild type, primarily because of an increase in γ-tocopherol content. This enlarged pool of γ-tocopherol was almost entirely converted to α-tocopherol by crossing HPT1 overexpressing plants with lines constitutively overexpressing γ-tocopherol methyltransferase. Seed of the resulting double overexpressing lines had a 12-fold increase in vitamin E activity relative to wild type. These results indicate that HPT activity is limiting in various Arabidopsis tissues and that total tocopherol levels and vitamin E activity can be elevated in leaves and seeds by combined overexpression of the HPT1 and γ-tocopherol methyltransferase genes.